A hexagon in Saturn’s northern stratosphere surrounding the emerging summertime polar vortex - L. N. Fletcher (Nature Portfolio, 2018)
The Cassini spacecraft has provided an unprecedented characterisation of seasonal changes on Saturn. Here the authors describe the development of a warm polar vortex in Saturn’s northern summer, and show that the hexagon extends hundreds of kilometres from the troposphere into the stratosphere.